(untitled) (Research, Society and Development, 2021)
This article aims to reveal understand the subjective relationships formed by a graduate of the Pedagogy Course in the non-school space. Therefore, we chose the following problem: how are subjective relations formed by a graduate of the Pedagogy course in the non-school space?The collaborator in our research is an alumnus of the Pedagogy course at the State University of Rio Grande do Norte - UERN, graduated in the context of the new curricular matrix, reformulated and implemented based on the new public policies for the Pedagogy course and who specializes in the hospital environment. The framework the oretical-methodological assumptions of the research are anchored in Socio-Historical Psychology in the light of Marx’s Historical-Dialectic materialism and in the studies of Vygotsky and his collaborators, Leontiev and Luria. This is a qualitative approach investigation, which adopted as a research procedure the reflective interview and for information analysis, the nuclei of meanings elaborated by Aguiar and Ozella. The condition posture of conditionof the pedagogue engaged in the collaborative hospital context with the research is modified according to the need she faces in the environment in which she is inserted to meet her various day-to-day needs.This change happens through the subjective experiences in the educational space in which this educator is inserted.